2017
DOI: 10.1002/pen.24772
|View full text |Cite
|
Sign up to set email alerts
|

Replication of surface micro‐features using variothermal injection molding: Application to micro‐fluidics

Abstract: We study injection molding of mesoscale items with µm‐scale surface features, namely micro‐fluidic channels, relating replication quality to process conditions. Using variothermal molding, the variables are the pre‐heat temperature of the cavity insert surface before melt injection and the mold cooling start time. Surface temperatures and in‐cavity melt pressures are continuously measured. Rounded upper corners of the micro‐channels are used as an index of replication quality. For polymethylmethacrylate the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Is also measured the shift in pressure at switchover between both sensors, ΔP, and the distance, Δx, between the in cavity sensors. [19] In the scenario of a flow through a rectangular section, it is possible to determine the shear stress, τ, according to the Poiseuille flow, using Equation (5) and the shear rate, _ γ, adjusted by the Rabinovitsch expression for a non-Newtonian fluid, for a rectangular section (calculation of equivalent cross section between the two sensors [see Figure 2, Equation (6)]). The viscosity, η, is determined using the ratio η = τ=_ γ:…”
Section: In Operando Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…Is also measured the shift in pressure at switchover between both sensors, ΔP, and the distance, Δx, between the in cavity sensors. [19] In the scenario of a flow through a rectangular section, it is possible to determine the shear stress, τ, according to the Poiseuille flow, using Equation (5) and the shear rate, _ γ, adjusted by the Rabinovitsch expression for a non-Newtonian fluid, for a rectangular section (calculation of equivalent cross section between the two sensors [see Figure 2, Equation (6)]). The viscosity, η, is determined using the ratio η = τ=_ γ:…”
Section: In Operando Viscositymentioning
confidence: 99%
“…In the case of a hot-cold cycle (variotherm process), they also allow changes in temperature to be controlled and managed. [13,19] For amorphous materials, a mold temperature close to, or often above the glass transition temperature, T g , gives better replication results. [9,20] However, this variotherm technique causes repeated thermal shocks to the mold, which in time leads to a drastically shorter production lifetime (by number of cycles), as well as longer cycle times than a conventional molding cycle.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5,14 ] In general, pattern structures, such as pattern size, shape, and aspect ratio, and molding conditions, such as melting temperature, mold temperature, injection pressure, and injection speed, affect the precision of replication. [ 15–19 ] Improved replication precision has been reported by adjusting molding methods such as rapid heating of mold surface, [ 20,21 ] vacuum molding, [ 22 ] and injection compression molding. [ 23,24 ]…”
Section: Introductionmentioning
confidence: 99%
“…[5,14] In general, pattern structures, such as pattern size, shape, and aspect ratio, and molding conditions, such as melting temperature, mold temperature, injection pressure, and injection speed, affect the precision of replication. [15][16][17][18][19] Improved replication precision has been reported by adjusting molding methods such as rapid heating of mold surface, [20,21] vacuum molding, [22] and injection compression molding. [23,24] Polymer resin, a material used in injection molding, is injected into the mold by an injection molding machine resulting in solidification of the resin followed by rapid decrease in its flowability, which makes it difficult for it to fill the nanostructure of the nano-pattern.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] Mold preheating before injection is an efficient technical solution also to improve replication of microfeatures. [ 20 ] In fact, experimental results revealed that mold Ra does resist the cavity filling of polymer melt in microinjection molding. [ 6 ] In order to improve mold replication in micromolding, an effort is necessary to fully understand the mechanisms at the basis of this interaction between mold and polymer.…”
Section: Introductionmentioning
confidence: 99%